Clinical presentation, causes and outcome of febrile episodes in a prospective cohort of HIV-infected patients. Issue 1 (2nd January 2017) - De Munter, Paul; Derdelinckx, Inge; Peetermans, Willy E.; Vanderschueren, Steven; Van Wijngaerden, Eric
Abstract: Background: Fever was frequently caused by opportunistic conditions in HIV-patients in the early years of the epidemic. Little is known about diagnostic spectrum and outcome of febrile episodes in patients with good access to antiretroviral therapy. Methods: We prospectively studied clinical presentation, diagnosis and outcome of febrile episodes in a contemporary cohort of HIV-patients with good access to antiretroviral therapy. Fever was defined as temperature 38.3 °C or higher, measured by a health care provider. Results: We found 220 febrile episodes in 146 patients. In 25.9% of episodes the patient had a CD4 less than 200/mm³ and in 78.6% the patient was on antiretroviral therapy. There were multiple episodes in 44 patients. A diagnosis was established in 91.8%. Infection accounted for 82.3%, mainly respiratory tract infections, viral syndromes and abdominal infections. Malignancy, drug reactions and inflammatory conditions accounted together for less than 12% of episodes. Fifteen percent were attributed to opportunistic conditions. Episodes in patients with CD4 less than 200 were less likely to be caused by infection, but more likely to be caused by malignancy, drug reactions and opportunistic conditions. In 6.4% the patient died within six months after the onset of fever. Risk factors for death at six months in multivariable analysis were higher age and lower CD4. Conclusions: HIV-patients with access to antiretroviral therapy present with fever mostly due to conditions common in the general population. HIV-patients with low CD4 remain at risk for fever due to opportunistic conditions and death.